Perspektif HAM terhadap Asas Praduga Tak Bersalah Pada Hukum Pidana Indonesia - Doodoh, Marthin; Tuwaidan, Herry F.D. (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
The principle of presumption of innocence is one of the fundamental principles in the judiciary that guarantees human rights (HAM). This study utilizes normative legal methods with a statutory regulatory approach, document analysis, and case studies to identify it in Indonesian criminal law. It is known that this principle is not only recognized in the national legal system, for example, the 1945 Constitution and the Criminal Procedure Code, but also in international conventions, such as UDHR) and ICCPR. Challenges to its implementation in Indonesia include public stigma on the accused, media pressure, and violations of legal procedures. The recommendation is to take strategic steps for strengthening the application of the principle of presumption of innocence and certainty of human rights in the Indonesian criminal justice system.